2020
DOI: 10.1002/mop.32699
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and design of enhanced decoupled UWB MIMO antenna for wearable applications

Abstract: A lightweight multi‐input multi‐output (MIMO) two‐element wearable ultra‐wideband (UWB) antenna having a port isolation of greater than 21 dB is introduced in this communication. The proposed structure includes wearable jeans cloth as a substrate, wherein two inverted u‐formed stubs are mounted in the middle position located on the backside of antenna and attached to the partially etched ground for enhancing the characteristics of port isolation. The developed UWB MIMO antenna has a size of 50 x 35 mm2 and cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…(D) shows the S11 versus frequency of the Super‐UWB MIMO antenna with respect to different length sizes of the ground plane. It can be found that the ground plane size influencing the impedance match, which is common case for UWB antennas 2,26–29 . In this design, length of the ground plane (Lg) of 11 mm has a good impedance match with S11 below −10 dB in the entire band of operation.…”
Section: Mimo Antenna Configuration and Analysismentioning
confidence: 96%
“…(D) shows the S11 versus frequency of the Super‐UWB MIMO antenna with respect to different length sizes of the ground plane. It can be found that the ground plane size influencing the impedance match, which is common case for UWB antennas 2,26–29 . In this design, length of the ground plane (Lg) of 11 mm has a good impedance match with S11 below −10 dB in the entire band of operation.…”
Section: Mimo Antenna Configuration and Analysismentioning
confidence: 96%
“…The lowest correlation corresponds to the better MIMO performance. The ECC in far-field for a multi-antenna model is expressed as [17]:…”
Section: Analysis Of the Obtained Mimo Performancementioning
confidence: 99%
“…The required value of the DG for the MIMO system should be around 10dB. The DG is a function of ECC and can be expressed as [17]:…”
Section: Analysis Of the Obtained Mimo Performancementioning
confidence: 99%
“…These contours are assumed to be distributed and represents the power concentration on the phantom model whenever the antenna emits an UWB signal into the phantom. The assessment of SAR values with standard distances available in the literature 12,14,20 are addressed in Table 6. Figure 22 demonstrates that the SAR values on the phantom model for 1 g of body tissue are 0.215, 0.463, 0.710 and 0.930 W/Kg (less than 1.6 W/Kg for 1 g tissue) at frequencies of 3.5, 5.8, 8.4 and 10.6 GHz which makes the suggested antenna totally safe for exposure in humans and ideal for MWI biomedical applications 24,56 …”
Section: Breast Phantom Design For Evaluation Of S‐parameters and Sar...mentioning
confidence: 99%
“…Nevertheless, they are the most appropriate and compatible antennas for MI of tumor tissues, but tradeoff exists due to limited bandwidth and big-size of the design. Although such antennas have an intrinsic limitation with the narrow bandwidth 4,9 so researchers use different kinds of feeding techniques, 10 such as offset fed patch antennas, 11 introduction of slots on patches, 12 using low-dielectric substrates, 13,14 increasing the thickness of a substrate 15 and so forth. to obtain large operating bandwidth, but with these methods, several performance characteristics degrades.…”
Section: Introductionmentioning
confidence: 99%